Hidden Curriculum as a Form of Cultivating Patriotism Values in State Civil Apparatus through College Hymns - Efendy, Rustan; Karim, Abdul Rahim; Jaya, Muh. Ilham; Jumaedi; Sari, Andi Nurindah (Universitas Pendidikan Ganesha, 2024)
The hidden curriculum has proven to be a challenging concept to understand and define. This research aims to explore the hidden curriculum development model as a new form of instilling the value of patriotism in the state civil apparatus in Indonesia through the massification of college hymns. Data were obtained through indepth interviews, participatory observation, and document study. Data analysis techniques were carried out before going to the field, while in the field and after completing the research using the NVivo application by reducing data, presenting data and drawing conclusions. The data validity test is carried out by credibility test, transferability test, dependability test and confirmability test. For the purposes of analyzing college hymns, the researchers used Ferdinand de Saussure's semiotic analysis. The results showed that the hidden curriculum model can instill the value of patriotism in the state civil apparatus in the Indonesian context. The cultivation of the value of patriotism is carried out by activities outside the effective working hours of the state civil apparatus through major university events, such as graduation activities, dies natalis, academic meetings, charity days, and independence day ceremonies. These activities function effectively in instilling the value of patriotism in the Indonesian context. The results show that state civil apparatus who often participate in activities in which the college hymn is sung have a strong tendency to love the country.